Predictors of cervical lymph node metastasis in salivary gland cancer - Ettl, Tobias; Gosau, Martin; Brockhoff, Gero; Schwarz-Furlan, Stephan; Agaimy, Abbas; Reichert, Torsten E.; Rohrmeier, Christian; Zenk, Johannes; Iro, Heinrich (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2014)
This study compares clinicopathological parameters with novel molecular markers for predicting cervical lymph node metastasis in salivary gland cancer.Three hundred sixteen salivary gland carcinomas were included in this study. Genomic epidermal growth factor receptor (EGFR), human epidermal growth factor receptor 2 (HER2), phosphatase and tensin homolog (PTEN), and hepatocyte growth factor receptor (MET) was determined by fluorescence in situ hybridization (FISH). Chi-square tests, multivariate regression, and Kaplan-Meier survival analysis were used for statistics.Nodal staging determines long-term survival. Clinicopathological parameters associated with positive neck nodes are advanced age (p = .006), T3/T4 classification, histological high-grade malignancy, and diagnosis of salivary duct carcinoma (p < .001 each). Neck node metastases also correlate with copy number gain of EGFR (p = .004) and HER2, aberration of MET, and deletion of PTEN (p < .001 each). Multivariate analysis showed SDC (p = .002) to be the strongest predictor of lymph node metastasis, followed by MET aberration (p = .009), T3/T4 classification (p = .017), PTEN deletion (p = .042), and adenocarcinoma not otherwise specified (NOS; p = .047).The histological subtype is crucial for decisions regarding neck dissection. New molecular parameters may also indicate elective treatment of the neck.
EVALuna2:6596